Global forests risk to climate and land-use change - Ernest F. Asamoah; Joseph M. Maina; Linda J. Beaumont; Hedley S. Grantham; James E.M. Watson (Biological Conservation, 2026)

Delivering the ocean climate actions: Building a robust information base to facilitate and enhance the incorporation of blue carbon solutions into Kenya’s climate commitments - Joseph KS Lang’at; James G. Kairo; George W. Maina; Caroline Wanjiru; Fredrick Mungai; Margaret A. Owuor; Josphat G. Nguu; Emily Landis (Marine Policy, 2026)

Temporal relationships among lunar crustal rocks - Lars E. Borg; Thomas S. Kruijer; Ming-Chang Liu; Autumn G. Roberts; Josh Wimpenny; Ouyanatu N.Z. Maina; Joseph Boro; Charles K. Shearer; Kyle M. Samperton (Geochimica et Cosmochimica Acta, 2025)

Livestock mobility in border towns and markets in Ghana: a retrospective analysis, 2017–2023 - Sherry Ama Mawuko Johnson; Theophilus Odoom; William Tasiame; Benita Anderson; Christiana Terkper; Richard Kwamena Abbiw; Kingsley Amoako; Akosua Kumi Nyarko; Fenteng Danso; Joseph Abuh; Meyir Ziekah; Anthony Akunzule; et al. (Tropical Animal Health and Production, 2025)

Design and management considerations for the Kenya–Tanzania marine transboundary conservation area - Vera Horigue; Arthur Tuda; Joseph Maina (Conservation Biology, 2025)
Although transboundary conservation areas (TCAs) are critical tools for protecting ecosystems and ecological processes that transcend national jurisdictions, they are challenging to create due to the differences in governance contexts and capacity and power dynamics among countries. Marine TCAs are also more difficult to enforce relative to terrestrial TCAs because most nations still treat oceans as open access. Current guidelines for TCA development and implementation also focus mostly on terrestrial TCAs, which are not practical for marine TCAs. Hence, we reviewed the challenges associated with the design and management of marine TCAs and devised analytical and practical approaches to support the application of spatial planning frameworks and adaptive governance mechanisms. We used the lessons from the review to examine the decisions made for the proposed marine TCA in the Kenya–Tanzania border region and created options and considerations to promote effective design and management processes. We found the obstacles to marine TCAs in general are related to issues of fit, particularly differences in environmental research capacity, socioeconomic contexts, and internal institutional arrangements. These included differences in knowledge and capacity for marine ecological research and conservation; ability to adjust and update data; differences in values, interests, and resource uses; conservation costs; jurisdictional differences; engagement of multiple levels of organization; and differences in legal bases and policy development processes. Understanding and reconciling these challenges during the TCA development process can help enhance meaningful discussions in the design of the TCA and cultivate the enabling conditions for collaborative governance across countries and within different levels of organization from national to local actors.

Diversification of refugia types needed to secure the future of coral reefs subject to climate change - Tim R. McClanahan; Emily S. Darling; Maria Beger; Helen E. Fox; Hedley S. Grantham; Stacy D. Jupiter; Cheryl A. Logan; Elizabeth Mcleod; Lisa C. McManus; Remy M. Oddenyo; Gautam S. Surya; Amelia. S. Wenger; et al. (Conservation Biology, 2024)
Identifying locations of refugia from the thermal stresses of climate change for coral reefs and better managing them is one of the key recommendations for climate change adaptation. We review and summarize approximately 30 years of applied research focused on identifying climate refugia to prioritize the conservation actions for coral reefs under rapid climate change. We found that currently proposed climate refugia and the locations predicted to avoid future coral losses are highly reliant on excess heat metrics, such as degree heating weeks. However, many existing alternative environmental, ecological, and life‐history variables could be used to identify other types of refugia that lead to the desired diversified portfolio for coral reef conservation. To improve conservation priorities for coral reefs, there is a need to evaluate and validate the predictions of climate refugia with long‐term field data on coral abundance, diversity, and functioning. There is also the need to identify and safeguard locations displaying resistance toprolonged exposure to heat waves and the ability to recover quickly after thermal exposure. We recommend using more metrics to identify a portfolio of potential refugia sites for coral reefs that can avoid, resist, and recover from exposure to high ocean temperatures and the consequences of climate change, thereby shifting past efforts focused on avoidance to a diversified risk‐spreading portfolio that can be used to improve strategic coral reef conservation in a rapidly warming climate.

Multivariate environment-fish biomass model informs sustainability and lost income in Indian Ocean coral reefs - Timothy R. McClanahan; Stephanie D’Agata; N.A.J. Graham; Maxwell Azali Kodia; Joseph M. Maina (Marine Policy, 2023)

Disentangling the influence of the economic development discourse on the management of national parks through systems thinking: Case studies from the Philippines and Mozambique - Vera Horigue; Russell Richards; Alima Taju; Joseph Maina (Land Use Policy, 2023)

Prioritization of invasive alien species with the potential to threaten agriculture and biodiversity in Kenya through horizon scanning - Joseph Mulema; Roger Day; Winnie Nunda; Komivi Senyo Akutse; Anani Y. Bruce; Sospeter Gachamba; Solveig Haukeland; Ruth Kahuthia-Gathu; Staline Kibet; Asenath Koech; Thomas Kosiom; Douglas Watuku Miano; et al. (Biological Invasions, 2022)
Invasive alien species (IAS) rank among the most significant drivers of species extinction and ecosystem degradation resulting in significant impacts on socio-economic development. The recent exponential spread of IAS in most of Africa is attributed to poor border biosecurity due to porous borders that have failed to prevent initial introductions. In addition, countries lack adequate information about potential invasions and have limited capacity to reduce the risk of invasions. Horizon scanning is an approach that prioritises the risks of potential IAS through rapid assessments. A group of 28 subject matter experts used an adapted methodology to assess 1700 potential IAS on a 5-point scale for the likelihood of entry and establishment, potential socio-economic impact, and impact on biodiversity. The individual scores were combined to rank the species according to their overall potential risk for the country. Confidence in individual and overall scores was recorded on a 3-point scale. This resulted in a priority list of 120 potential IAS (70 arthropods, 9 nematodes, 15 bacteria, 19 fungi/chromist, 1 viroid, and 6 viruses). Options for risk mitigation such as full pest risk analysis and detection surveys were suggested for prioritised species while species for which no immediate action was suggested, were added to the plant health risk register and a recommendation was made to regularly monitor the change in risk. By prioritising risks, horizon scanning guides resource allocation to interventions that are most likely to reduce risk and is very useful to National Plant Protection Organisations and other relevant stakeholders.

Policy gaps in the East African Blue economy: Perspectives of small-scale fishers on port development in Kenya and Tanzania - Pascal Thoya; Vera Horigue; Christian Möllmann; Joseph Maina; Kerstin S. Schiele (Frontiers in Marine Science, 2022)
Recently, the rights of small-scale fishers have increasingly been acknowledged in ocean governance because coastal development and various maritime activities have reduced traditional fishing grounds. More specifically, small-scale fisheries (SSF) are increasingly being threatened by ocean grabbing, pollution, and a lack of inclusiveness in decision-making processes. Although there are guidelines to resolve and reduce conflict, formal avenues to include fisher concerns, particularly in the context of ocean development and governance, remain a difficult task. Moreover, there is insufficient information on how fishers are impacted by coastal and marine development and how their concerns are included in the decision-making process. Hence, this study contributes to the SSF discourse by understanding and describing the characteristics and concerns of small-scale fishers from two coastal towns in East Africa with different levels of port development. Using data from perception surveys, focus group discussions, and participatory mapping, we discuss how fishers were involved in the decision-making processes to develop ports in Lamu, Kenya, and Bagamoyo, Tanzania. We found that fishers rely on nearshore ecosystems such as mangroves and coral reefs because of their accessibility since most fishers only use low-powered boats for fishing. Moreover, we found that the fishers’ livelihoods were severely affected by port development and that they were excluded from the decision-making process concerning the port’s construction and fishers’ compensations. While some fishers believe that new ports in the region can increase their livelihoods by creating new markets and jobs, this is unlikely to happen since most fishers are not qualified to work in formal port-related jobs. We propose three steps that will allow fishermen to participate in port development decision-making processes and contribute to the development of a sustainable SSF. These include improving engagement with fishers to allow meaningful participation in decision-making, developing a blue economy policy focused on SSF, and implementing maritime spatial planning.

Large geographic variability in the resistance of corals to thermal stress - Timothy R. McClanahan; Joseph M. Maina; Emily S. Darling; Mireille M. M. Guillaume; Nyawira A. Muthiga; Stephanie D’agata; Julien Leblond; Rohan Arthur; Stacy D. Jupiter; Shaun K. Wilson; Sangeeta Mangubhai; Ali M. Ussi; et al. (Global Ecology and Biogeography, 2020)
Aim Predictions for the future of coral reefs are largely based on thermal exposure and poorly account for potential geographic variation in biological sensitivity to thermal stress. Without accounting for complex sensitivity responses, simple climate exposure models and associated predictions may lead to poor estimates of future coral survival and lead to policies that fail to identify and implement the most appropriate interventions. To begin filling this gap, we evaluated a number of attributes of coral taxa and communities that are predicted to influence coral resistance to thermal stress over a large geographic range. Location Western Indo‐Pacific and Central Indo‐Pacific Ocean Realms. Major taxa studied Zooxanthellate Scleractinia – hard corals. Methods We evaluated the geographic variability of coral resistance to thermal stress as the ratio of thermal exposure and sensitivity in 12 countries during the 2016 global‐bleaching event. Thermal exposure was estimated by two metrics: (a) historical excess summer heat (cumulative thermal anomaly, CTA), and (b) a multivariate index of sea‐surface temperature (SST), light, and water flow (climate exposure, CE). Sensitivity was estimated for 226 sites using coordinated bleaching observations and underwater surveys of coral communities. We then evaluated coral resistance to thermal stress using 48 generalized linear mixed models (GLMMs) to compare the potential influences of geography, historical SST variation, coral cover and coral richness. Results Geographic faunal provinces and ecoregions were the strongest predictors of coral resistance to thermal stress, with sites in the Australian, Indonesian and Fiji‐Caroline Islands coral provinces having higher resistance to thermal stress than Africa‐India and Japan‐Vietnam provinces. Ecoregions also showed strong gradients in resistance with highest resistance to thermal stress in the western Pacific and Coral Triangle and lower resistance in the surrounding ecoregions. A more detailed evaluation of Coral Triangle and non‐Coral Triangle sites found higher resistance to thermal stress within the Coral Triangle, associated with c. 2.5 times more recent historical thermal anomalies and more centralized, warmer, and cool‐water skew SST distributions, than in non‐Coral Triangle sites. Our findings identify the importance of environmental history and geographic context in future predictions of bleaching, and identify some potential drivers of coral resistance to thermal stress. Main conclusions Simple threshold models of heat stress and coral acclimation are commonly used to predict the future of coral reefs. Here and elsewhere we show that large‐scale responses of coral communities to heat stress are geographically variable and associated with differential environmental stresses and histories.

Climate‐driven shift in coral morphological structure predicts decline of juvenile reef fishes - Luisa Fontoura; Kyle J. A. Zawada; Stephanie D’agata; Mariana Álvarez‐Noriega; Andrew H. Baird; Nader Boutros; Maria Dornelas; Osmar J. Luiz; Joshua S. Madin; Joseph M. Maina; Oscar Pizarro; Damaris Torres‐Pulliza; et al. (Global Change Biology, 2020)
Rapid intensification of environmental disturbances has sparked widespread decline and compositional shifts in foundation species in ecosystems worldwide. Now, an emergent challenge is to understand the consequences of shifts and losses in such habitat‐forming species for associated communities and ecosystem processes. Recently, consecutive coral bleaching events shifted the morphological makeup of habitat‐forming coral assemblages on the Great Barrier Reef (GBR). Considering the disparity of coral morphological growth forms in shelter provision for reef fishes, we investigated how shifts in the morphological structure of coral assemblages affect the abundance of juvenile and adult reef fishes. We used a temporal dataset from shallow reefs in the northern GBR to estimate coral convexity (a fine‐scale quantitative morphological trait) and two widely used coral habitat descriptors (coral cover and reef rugosity) for disentangling the effects of coral morphology on reef fish assemblages. Changes in coral convexity, rather than live coral cover or reef rugosity, disproportionately affected juvenile reef fishes when compared to adults, and explained more than 20% of juvenile decline. The magnitude of this effect varied by fish body size with juveniles of small‐bodied species showing higher vulnerability to changes in coral morphology. Our findings suggest that continued large‐scale shifts in the relative abundance of morphological groups within coral assemblages are likely to affect population replenishment and dynamics of future reef fish communities. The different responses of juvenile and adult fishes according to habitat descriptors indicate that focusing on coarse‐scale metrics alone may mask fine‐scale ecological responses that are key to understand ecosystem functioning and resilience. Nonetheless, quantifying coral morphological traits may contribute to forecasting the structure of reef fish communities on novel reef ecosystems shaped by climate change.

Simulating streamflow in the Upper Halda Basin of southeastern Bangladesh using SWAT model - Farzana Raihan; Linda J. Beaumont; Joseph Maina; Akm Saiful Islam; Sandy P. Harrison (Hydrological Sciences Journal, 2020)

MDPI Oceans: A New Publication Channel for Open Access Science Focused on the Ocean - Antonio Bode; Fátima Abrantes; Agostinho Antunes; Alvise Benetazzo; Chen-Tung Arthur Chen; Emmanuel Devred; Martin Gade; Eulàlia Gràcia; Jochen Horstmann; Diego Macías; Joseph M. Maina; Pere Masqué; et al. (Oceans, 2019)
The ocean is the most important subsystem of the Earth’s climate system and functions as its heart, regulating the energy distribution of the planet [...]

Revisiting “Success” and “Failure” of Marine Protected Areas: A Conservation Scientist Perspective - Sylvaine Giakoumi; Jennifer McGowan; Morena Mills; Maria Beger; Rodrigo H. Bustamante; Anthony Charles; Patrick Christie; Matthew Fox; Pablo Garcia-Borboroglu; Stefan Gelcich; Paolo Guidetti; Peter Mackelworth; et al. (Frontiers in Marine Science, 2018)

Thermal energy and stress properties as the main drivers of regional distribution of coral species richness in the Indian Ocean - Mebrahtu Ateweberhan; Tim R. McClanahan; Joseph Maina; Charles Sheppard (Journal of Biogeography, 2018)
Aim Large‐scale variation in species richness results from multiple environmental controls. We proposed to identify the main factors that influence species richness of reef corals to provide insight into natural forces and their implications for future climate impacts. Location Indian Ocean. Methods We applied quantile regression ( QR ) to predict coral species richness and to evaluate the influence of reef area, biogeographical connection – represented by reef area up‐current, geological provinces defined by plate tectonics, latitude, longitude and mainland‐island separation, the physico‐chemical factors of photosynthetically active radiation ( PAR ), salinity and primary productivity and seven properties of sea surface temperature (mean, minimum, maximum, standard deviation, range, kurtosis and skewness) on coral species richness. Predictions at three quantiles (0.50, 0.75 and 0.95) were compared against ordinary least squares regression ( OLS ) analysis. Results All four models successfully predicted species richness, with the 95% QR model showing the best fit. According to this model, reef area, number of reefs up‐current and mean‐ SST had positive effects while maximum and kurtosis‐ SST had negative effects on richness. The distribution of observed richness values in relation to the regression line suggested this model revealed the main limiting factors. High predicted richness sites were located in the region from Western Australia to Central Indian Ocean Islands and southern India, the Mozambique Channel and East Africa and Southern Red Sea and Gulf of Aden. Sites with low predicted richness were Arabian/Persian Gulf and Gulf of Oman, South Africa and south‐west Madagascar, Gulf of Kutch, Bay of Bengal and the Mascarenes. Conclusions Temperature properties played a prominent role in influencing species richness mainly as latent energy and stress rather than thermal stability. These thermal properties indicate the conditions needed to promote coral diversity and selecting climate refugia for conservation management.

Integrating social–ecological vulnerability assessments with climate forecasts to improve local climate adaptation planning for coral reef fisheries in Papua New Guinea - Joseph Maina; Justus Kithiia; Josh Cinner; Ezra Neale; Sylvia Noble; Daniel Charles; James E.M. Watson (Regional Environmental Change, 2016)

Regional coral responses to climate disturbances and warming is predicted by multivariate stress model and not temperature threshold metrics - Timothy R. McClanahan; Joseph Maina; Mebrahtu Ateweberhan (Climatic Change, 2015)

Mangrove vulnerability modelling in parts of Western Niger Delta, Nigeria using satellite images, GIS techniques and Spatial Multi-Criteria Analysis (SMCA) - Omo O. Omo-Irabor; Samuel B. Olobaniyi; Joe Akunna; Valentijn Venus; Joseph M. Maina; Charles Paradzayi (Environmental Monitoring and Assessment, 2011)

Introgressive hybridization of human and rodent schistosome parasites in western Kenya - MICHELLE L. STEINAUER; BEN HANELT; IBRAHIM N. MWANGI; GEOFFREY M. MAINA; LELO E. AGOLA; JOSEPH M. KINUTHIA; MARTIN W. MUTUKU; BEN N. MUNGAI; WADE D. WILSON; GERALD M. MKOJI; ERIC S. LOKER (Molecular Ecology, 2008)
Hybridization and introgression can have important consequences for the evolution, ecology and epidemiology of pathogenic organisms. We examined the dynamics of hybridization between a trematode parasite of humans, Schistosoma mansoni , and its sister species, S. rodhaini , a rodent parasite, in a natural hybrid zone in western Kenya. Using microsatellite markers, rDNA and mtDNA, we showed that hybrids between the two species occur in nature, are fertile and produce viable offspring through backcrosses with S. mansoni . Averaged across collection sites, individuals of hybrid ancestry comprised 7.2% of all schistosomes collected, which is a large proportion given that one of the parental species, S. rodhaini, comprised only 9.1% of the specimens. No F1 individuals were collected and all hybrids represented backcrosses with S. mansoni that were of the first or successive generations. The direction of introgression appears highly asymmetric, causing unidirectional gene flow from the rodent parasite, S. rodhaini, to the human parasite, S. mansoni. Hybrid occurrence was seasonal and most hybrids were collected during the month of September over a 2‐year period, a time when S. rodhaini was also abundant. We also examined the sex ratios and phenotypic differences between the hybrids and parental species, including the number of infective stages produced in the snail host and the time of day the infective stages emerge. No statistical differences were found in any of these characteristics, and most of the hybrids showed an emergence pattern similar to that of S. mansoni. One individual, however, showed a bimodal emergence pattern that was characteristic of both parental species. In conclusion, these species maintain their identity despite hybridization, although introgression may cause important alterations of the biology and epidemiology of schistosomiasis in this region.

Observations of a new source of coral mortality along the Kenyan coast - Timothy R. McClanahan; Shawn M. McLaughlin; Joanne E. Davy; William H. Wilson; Esther C. Peters; Kathy L. Price; Joseph Maina (Hydrobiologia, 2004)